Effect of Ganoderma lucidum polysaccharides as immunostimulants against Vibrio harveyi in pearl gentian grouper (♀Epinephelus fuscoguttatus × ♂Epinephelus lanceolatus) - Zhang, Yilin; Zhong, Jian; Huang, Yucong; Jian, Jichang; Cai, Shuanghu (Frontiers in Marine Science, 2022)
Immunostimulants are becoming one of the most effective models for healthy and sustainable development against vibriosis, which is a serious threat to the global aquaculture industry. This study evaluated the effects of different concentrations of Ganoderma lucidum polysaccharides (GLPs) on the immunomodulation and disease resistance of pearl gentian groupers. The relative percent survival of the pearl gentian groupers challenged with Vibrio harveyi ZJ0603 by intraperitoneal injection reached 53.3, 60, 70, and 73.3% in the GLPs2, GLPs4, GLPs6, and GLPs8 groups, respectively, which are significantly higher than that of 33.3% in the control group. Meanwhile, the expression levels of immune-relative genes, including IgM, MHC-Iα, MHC2, IL-1β, and TNF-α, were upregulated in the liver, spleen, head kidney, and thymus within 28 days after GLP injection. The total serum protein and the activities of catalase, superoxide dismutase, and lysozymes in serum were significantly upregulated in all GLP groups compared with those in the control. Moreover, the optimal immunity effect was observed with an injection of GLPs at concentrations of 6 or 8 mg/ml. The results demonstrate that GLPs were an effective immunostimulant, enhancing both specific and non-specific immunity as well as disease resistance in pearl gentian grouper.